Protecting Children Rights through the Juvenile Criminal Justice System in Indonesia: Issues and Challenges - Susila, Muh Endriyo; Yonar, Bagaskara (JURNAL MERCATORIA, 2024)
The Juvenile Criminal Justice System is established to uphold justice for children who engage in criminal proceedings, especially those who perpetrate criminal offense. The System sets up various measures in order to protect the rights of these children. This article aims at evaluating the operation of the Juvenile Criminal Justice System in Indonesia with special concern on the fulfilment of the rights of children who are in conflict with the law. The type of research is that of normative legal research which relies on secondary data in the form of primary and secondary legal material. This normative legal research employs statutory approach. It is found that the rights of children who are in conflict with the law is primary protected through the employment of diversion, the initial step for settling the criminal case outside the judicial system. The operation of the Juvenile Criminal Justice System comes across some obstacles in field, including with regard to the employment of diversion. Therefore, improvement in employing diversion seems to be necessary to achieve better quality of children rights protection.